New synthetic route for 1,2-diketo compounds using unexpected C-C bond cleavage by PCC - Bhosale, Shrikar M.; Momin, Aadil A.; Gawade, Rupesh L.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Tetrahedron Letters, 2012)
An efficient method has been established for the preparation of 1,2-diketones by unexpected C-C bond cleavage in 4-keto-2-hydroxy esters using pyridiniumchlorochromate (PCC). (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: 1; 2-Diketones; C-C bond cleavage; PCC

Unexpected observations during the total synthesis of calothrixin B-sodium methoxide as a source of hydride - Bhosale, Shrikar M.; Momin, Aadil A.; Kunjir, Shrikant; Rajamohanan, P. R.; Kusurkar, Radhika S. (Tetrahedron Letters, 2014)
During the total synthesis of calothrixin B, various novel and unexpected results were noticed such as cleavage of C-N bond in imine using sodium cyanoborohydride, sodium methoxide as a hydride source for reduction, deformylation in the presence of bromine, and deacylation using ceric ammonium nitrate (CAN). A detailed mechanism has been proposed for the unexpected results and a few of them are generalized. Temperature dependent NMR studies have been carried out for confirmation of the structure of one of the intermediates in the synthetic sequence. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Azoxybenzene; Calothrixin B; reduction; Sodium cyanoborohydride; Sodium methoxide